Navigating rhetoric in academic writing: Key structures in effective dissertation - Rochma, Anis Firdatul; Nurhayati, Endang; Widodo, Pratomo; Triastuti, Anita; Musfiroh, Tadkiroatun (Directorate of Research and Community ServiceUniversitas Negeri Yogyakarta, 2024)
A dissertation represents a key academic work produced by doctoral students as a requirement for graduation and the attainment of a doctoral degree. Consequently, doctoral candidates are expected to demonstrate strong and precise dissertation writing skills. This study aims to (1) analyze the rhetorical structures employed in each section of dissertations authored by doctoral students in the Doctoral Program in Language Education, and (2) compare these rhetorical structures with established academic writing conventions. The research utilizes a mixed-methods approach, adopting the textual organization framework of the Academic Phrasebank by Morley (2014) as the primary guide, supplemented by Santos' (1996) framework for abstract structure. Data collection includes both qualitative and quantitative components. The data analysis is conducted using AntConc 4.0.11, developed by Laurence Anthony from Waseda University, with an emphasis on calculating the frequency of words, phrases, collocations, concordances, and specific expressions within the dissertations. The findings reveal distinctive rhetorical patterns in the abstract, introduction, literature review, methodology, results, discussion, and conclusion sections of the dissertations produced by doctoral students within the field of Language Education.